Building communities in academia - Aarnikoivu, Melina; Le, Ai Tam (Surviving and thriving in academia, 2024)
This book contains an Open Access chapter. Communities exist everywhere in academia. They are important not only for facilitating academic socialisation and generating intellectual capital, but also for fostering academic wellbeing. But how do communities come to be and how do we develop and maintain them? What kinds of challenges are involved when bringing people together around a shared interest in a field or topic? Addressing community-building in academia through a practical yet critical lens, the nine chapters present cases of academic community-building, or lack thereof, from across the globe. These communities are built and maintained by scholars representing different career stages, resulting in a go-to resource for any academic or higher education practitioner interested in community-building activities that strengthen and emphasise the collective - rather than competitive - aspect of academic work. Communities bring various benefits, yet community builders encounter several challenges. Very often, community-building often takes a great deal of time and (often voluntary) effort that is rarely officially rewarded. Building Communities in Academia poses important questions and provides extensive insights that scholars and practitioners can use when developing community-related activities to enhance connection in academia.